2019
DOI: 10.1097/mlr.0000000000001208
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Pain Treatment

Abstract: Background: Despite the critical role that Emergency Medical Services (EMS) provides in the health care system, racial/ethnic treatment disparities in EMS remain relatively unexamined. Objective: To investigate racial/ethnic treatment disparities in pain assessment and pain medication administration in EMS. Research Design: A retrospective analysis was performed on 25,732 EMS encounters from 2015 to 2017 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…All of the studies assessed Hispanics' experiences with the EMS system in the United States, although some studies focused on the national (n = 15), 2,7,10,11,13,16,21,22,24,28,31,35,36,40,41 state (n = 11), 6,14,15,17,18,20,25,39,42,44,46 or local level (n = 17). 12,19,23,26,27,29,30,[32][33][34]37,38,45,[47][48][49] Hispanic sample size ranged from 1 to 99 (n = 4), 14,32,40,42,47 100 to 999 (n = 17), 12,18,19,27,…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies assessed Hispanics' experiences with the EMS system in the United States, although some studies focused on the national (n = 15), 2,7,10,11,13,16,21,22,24,28,31,35,36,40,41 state (n = 11), 6,14,15,17,18,20,25,39,42,44,46 or local level (n = 17). 12,19,23,26,27,29,30,[32][33][34]37,38,45,[47][48][49] Hispanic sample size ranged from 1 to 99 (n = 4), 14,32,40,42,47 100 to 999 (n = 17), 12,18,19,27,…”
Section: Resultsmentioning
confidence: 99%
“…22 On a more general basis, myriad studies have demonstrated that BIPOC patients have historically been less likely to receive opioid analgesia than are White patients across ages and painful conditions. [23][24][25][26][27][28][29][30][31][32][33] Unfortunately, recent studies continue to demonstrate that BIPOC patients presenting with painful conditions continue to face disadvantages regarding assessment and treatment in EDs, [34][35][36][37][38] with patient perceptions of this disparity serving as a barrier to even seeking emergency care. 39 Similarly, a 2018 study of traumatically injured individuals requiring emergency medical services (EMS) transport to hospitals found that significantly fewer Black patients received opioids prehospital compared to other ethnic groups.…”
Section: Racism In Pain Medicine: a Review Of The Literaturementioning
confidence: 99%
“…40 Similar findings were obtained from a more recent study. 34 Studies have found that implicit bias among providers affects their clinical judgement, decisions and behavior. Racial and ethnic stereotypes also influence assessments and treatment, especially with high pain intensity self-report among BIPOC patients.…”
Section: Racism In Pain Medicine: a Review Of The Literaturementioning
confidence: 99%
“…Additionally, quantification of pain is important because there is increasing concern that gender, race, age, and intellectual development disabilities may be involved in diagnostic delays as well as overtreatment or undertreatment of pain. 8 , 23 , 52 , 66…”
Section: Introductionmentioning
confidence: 99%